If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 + -3x = 3x + -5 Reorder the terms: -6 + 5x + -3x = 3x + -5 Combine like terms: 5x + -3x = 2x -6 + 2x = 3x + -5 Reorder the terms: -6 + 2x = -5 + 3x Solving -6 + 2x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 2x + -3x = -5 + 3x + -3x Combine like terms: 2x + -3x = -1x -6 + -1x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -1x = -5 + 0 -6 + -1x = -5 Add '6' to each side of the equation. -6 + 6 + -1x = -5 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -5 + 6 -1x = -5 + 6 Combine like terms: -5 + 6 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 5(1-w)+3=26+(-3) | | x-1/3=1/2 | | -5x+3y=25 | | 5(1+w)+3=26+3 | | -.6+.05x=5.3 | | -5y+3y=25 | | x+x+2+x+4+x+6=360 | | 23x+8-26=6-7 | | y^2+y=-10 | | x+1/4=7/4 | | 6(6-1)=4n-n | | 2n(3n-12)=0 | | x+x+2+x+4+x=360 | | x^2+3x+9/4 | | 7x+4=-5+3x+17 | | 2+4(y+1)=20+6 | | x+3/2=3/2 | | 7+2x+x=29+(-4) | | 6=3x-25 | | 7234.56=3.14r^2 | | 4t^4+18t^3-10t^2=0 | | x-5.5=-6.3 | | 5x-2(-7x+11)=16 | | (2/5n)7 | | j+(0.5*j-8)=100 | | x^2+3x-50=0 | | 7-7x-2=-22+3x-13 | | 7/5=10.5b | | 10b^2-26b+12=0 | | X/3-5=-4 | | 8-y=15 | | 5x=-5y+65 |